THE ROLE OF MASJID SYUHADA’S EDUCATION IN FORMING MODERATE MUSLIM IDENTITY - Mukhsin Achmad; Maulidia Mulyani (Yayasan Pendidikan Dan Pengembangan Harapan Ananda, 2026)
This Community Service (PkM) activity (1) aims to examine the educative role of Masjid Syuhada in forming a moderate Muslim identity and navigating urban polarization. This activity (2) applies the Asset-Based Community Development (ABCD) method, utilizing four systematic stages: asset mapping, building connections through interactive dialogue, co-creating visions, and driving community-led actions. The PkM program (3) was conducted at Masjid Syuhada in the pluralistic urban environment of Yogyakarta. The (4) main outcomes show that Masjid Syuhada successfully implements an integrative, eclectic educational spectrum by synthesizing five historical pillars: Kraton, Muhammadiyah, Tamansiswa, Islamic Boarding School (NU), and Western education. Furthermore, the mosque actively counteracts urban Muslim polarization by organizing moderate Islamic studies, facilitating dialogue spaces between diverse Muslim groups, and developing inclusive social programs. The (5) implication of this activity is the strengthening of a balanced wasatiyyah identity among key community actors including teachers, parents, foundation management, and youth thereby building grassroots social cohesion and resilience against exclusive and radical religious ideologies.